2021
DOI: 10.1097/corr.0000000000001837
|View full text |Cite
|
Sign up to set email alerts
|

THAs Performed Within 6 Months of Clostridioides difficile Infection Are Associated with Increased Risk of 90-Day Complications

Abstract: Background Clostridioides difficile infection (CDI) may be a surrogate for poor patient health. As such, a history of CDI before THA may be used to identify patients at higher risk for postoperative CDI and complications after THA. Investigations into the associations between CDI before THA and postoperative CDI and complications are lacking. Questions/purposes We compared the (1) frequency and potential risk factors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…1,2 However, history of CDI is missing from these recommendations despite its strong associations with recurrence and poor outcomes following lower extremity arthro-plasty. [7][8][9] Furthermore, an improved understanding of whether CDI is a modifiable or nonmodifiable risk factor, given its high recurrence rate, is needed. 10 Additionally, a temporal relationship between CDI and subsequent operations has been reported but is limited to THA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 However, history of CDI is missing from these recommendations despite its strong associations with recurrence and poor outcomes following lower extremity arthro-plasty. [7][8][9] Furthermore, an improved understanding of whether CDI is a modifiable or nonmodifiable risk factor, given its high recurrence rate, is needed. 10 Additionally, a temporal relationship between CDI and subsequent operations has been reported but is limited to THA.…”
Section: Discussionmentioning
confidence: 99%
“…10 Additionally, a temporal relationship between CDI and subsequent operations has been reported but is limited to THA. 7 We sought to examine patients who were diagnosed with CDI more than and within 6 months prior to a TKA, as well as comparison to a control cohort of patients without history of CDI. Patients who developed CDI within 6 months prior to TKA were associated with the highest odds of encountering 90-day CDI, medical/surgical complications, as well as increased readmissions and prolonged lengths of stay.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that after 6 months following C. difficile infection, the risk of complications following THA decreased, suggesting that the patient’s health improves after successful resolution of the C . difficile infection [2]. The findings from this study indicate that for patients with a history of C. difficile infection, surgeons should delay hip replacement for at least 6 months after treatment of the infection.…”
Section: Where Are We Now?mentioning
confidence: 96%
“…The current study by Douglas et al [2] identifies another important modifiable risk factor: duration of time after treatment of Clostridioides difficile infection. The occurrence of C .…”
Section: Where Are We Now?mentioning
confidence: 99%
See 1 more Smart Citation